1993
DOI: 10.1021/bi00096a003
|View full text |Cite
|
Sign up to set email alerts
|

Increasing sequence length favors .alpha.-helix over 310-helix in alanine-based peptides: Evidence for a length-dependent structural transition

Abstract: Ala-based peptides form marginally stable helices at low temperature and are conventionally considered as mixtures of alpha-helix and random coil. However, recent work with doubly spin-labeled peptides suggests that short 16-residue sequences contain a significant fraction of 3(10)-helix near the N-terminus (positions 4-8). Using the same double-label strategy, we report on the helix geometry of the peptides Ac-(AAAAK)nA-NH2 with n = 3 and n = 4. The 16-mer (n = 3) is now examined at a region near the C-termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
96
5

Year Published

1995
1995
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(118 citation statements)
references
References 26 publications
17
96
5
Order By: Relevance
“…To test the method, alanine-based a-helical peptides were synthesized (8,19,20). In 20 mol % trifluoroethanol, these are known to be a-helices.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To test the method, alanine-based a-helical peptides were synthesized (8,19,20). In 20 mol % trifluoroethanol, these are known to be a-helices.…”
Section: Methodsmentioning
confidence: 99%
“…[7] Thus, the average splitting (2B) for a given P(r), and subsequently the average separation of the two nitroxides, is obtained from: [8] and (r) = (Q.75(-)geI3/(2B)) * [9] The variance Sr of P(r) is also calculated from M(B):…”
Section: M(b)mentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have provided detailed microscopic knowledge of the folding energy landscape of these isolated motifs. Theoretical simulations have suggested that 3 10 -helices and/or type III -turns may serve as intermediates in the R-helix folding pathway (34)(35)(36)(37)(38)(39). The formation of kinetic intermediates such as -turn or 3 10 -helix lowers the entropic cost of nucleating the first helical residue, thus facilitating the helix folding transition (34,40,41).…”
mentioning
confidence: 99%
“…Recent ESR (39,42) and NMR (43) work by Millhauser et al (41) suggests the presence of 3 10 -helix at the terminus of short alanine-based helical peptides. The authors proposed that 3 10 -helices are a relic of the folding process.…”
mentioning
confidence: 99%